2020
DOI: 10.3892/or.2020.7779
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of LINC01554 and its co‑expressed genes in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related morbidity and mortality globally. Despite the remarkable improvements in comprehensive HCC treatment, the underlying mechanistic details of HCC remain elusive. We screened HCC patients for differentially expressed genes (DEGs) using the Gene Expression Omnibus (GSE113850) and The Cancer Genome Atlas (TCGA) datasets. LINC01554 expression in 40 paired samples was determined by quantitative reverse transcription polymerase chain reaction (RT-qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…In our study, results showed that NSCLC cell proliferation could be inhibited by overexpressed LINC01554 both in vivo and in vitro. The above results were in accordance with the previous study [2,12,19,20], which indicated that LINC01554 played a tumour suppressive role in NSCLC development.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, results showed that NSCLC cell proliferation could be inhibited by overexpressed LINC01554 both in vivo and in vitro. The above results were in accordance with the previous study [2,12,19,20], which indicated that LINC01554 played a tumour suppressive role in NSCLC development.…”
Section: Discussionsupporting
confidence: 93%
“… 26 , 27 It has been reported that low expression of LINC01554 is significantly correlated with overall survival, pathological stage, hepatitis B infection, tumor size, portal vein tumor thrombus and TNM stage. 28 This is consistent with our finding that low expression of LINC01554 indicates a poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, three survivalrelated LncRNAs, AC079061, AL354872, and LINC01093, were identified, and these LncRNAs had a strong correlation with RCL1 expression. LINC01093 has been shown to be significantly downregulated in HCC and was correlated with tumor cell proliferation and metastasis [31][32][33]. However, the function of AC079061 and AL354872 in HCC remained unclear.…”
Section: Discussionmentioning
confidence: 99%